Effect of spinal cord injury upon prostate: adenocarcinoma of prostate in a spinal cord injury patient - a case report - Vaidyanathan, Subramanian (BioMed Central, 2009)
INTRODUCTION: Following spinal cord injury, prostate undergoes atrophy probably due to interruption of neuro-hormonal pathways. The incidence of carcinoma of prostate is lower in patients with spinal cord injury above T-10 than in those with lesion below T-10. CASE PRESENTATION: A Caucasian male sustained T-4 paraplegia in 1991 at the age of 59-years. He had long-term indwelling urethral catheter. In May 1995, routine blood test showed prostate-specific antigen to be 17.7 mg/ml. Prostate biopsy revealed moderately differentiated primary adenocarcinoma of prostate; Gleason score was 3+3. Bone scans showed no evidence of metastatic bone disease. Bilateral orchidectomy was performed in September 1995. MRI of pelvis revealed no evidence of spread beyond prostatic capsule. There was no pelvic lymphadenopathy. In October 1996, this patient got chest infection and recovered fully after taking amoxicillin. In February 2001, he developed pneumonia and was prescribed cefuroxime intravenously. In March 2001, cystoscopy and electrohydraulic lithotripsy of vesical calculi were carried out. In August 2001, this patient was admitted to spinal unit for management of pressure sores. He expired on 28 June 2002 in local hospital. Cause of death was recorded as acute ventricular failure, congestive heart failure, chronic respiratory failure and spinal cord injury. CONCLUSION: Although prostate gland undergoes atrophy in men who sustained spinal cord injury in early age, physicians should be vigilant and look for prostatic diseases particularly in men, who have sustained spinal cord injury during later period of life. Patients with cervical and upper dorsal lesions are at risk of developing potentially life-threatening chest complications after major surgical procedures including radical prostatectomy. Therefore, it may be advisable to consider chemoprevention of prostate cancer with Finasteride, especially in men, who sustained cervical and upper dorsal spinal cord injury during later part of their life.